Health management: fashion trend or promising investment? Overview of corporate health promotion programs - O. V. Andropova (Klinicist)
Cardiovascular diseases are the leading cause of disability, premature mortality and economic loss worldwide. Despite the proven effectiveness of preventive measures in reducing the risks of development and progression of cardiovascular diseases, these programs are the most difficult to implement. 75–90 % of visits to primary care physicians in Western Europe and the United States are associated with physical fatigue and stress disorders, back pain and injuries. Studies have shown that workers with risk factors for chronic noncommunicable diseases are often absent from the workplace, have a higher level of disability and lower labor productivity. A worker with depression costs the employer almost 1,5 times more expensive than people without diseases. Elevated glucose levels, arterial hypertension, smoking and obesity cause an increase in the employer’s medical expenses by 34,8; 31,6; 31 and 27,4 %, respectively. The cost of US employers to pay for medical services, to compensate for the absence or ineffective presence due to illness costs $ 200 billion annually – more than $ 1,500 per employee.The health of workers is determined by both risk factors specific to the workplace and general population and individual risks..Modern technologies of health management, changing the profile of the health of labor collectives, can improve the image of the employer and increase the profitability of companies. The return on investment in corporate health programs is from 3 to 10 US dollars for each dollar invested. The programs implemented at the enterprises of the Russian Federation made it possible to reduce the duration of diseases with disability by 20–30 %, reduce mortality and the initial exit to disability by 45–60 %. The widespread introduction of the most effective corporate wellbeing programs of workers in the activities of medical organizations and companies of various profiles will ensure the implementation of the national projects “Healthcare” and “Demography”.